2021
DOI: 10.1016/j.numecd.2020.10.013
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 disease and nutritional choices: How will the pandemic reconfigure our food psychology and habits? A case study of the Italian population

Abstract: Background and Aims In Italy, the spread of the novel coronavirus (SARS-Cov-2) required lifestyle changes that have affected food choices and people’s health condition. We explore people’s perception of the role of food consumption as a preventive measure and how it reconfigures consumption habits. Method and Results We conducted an online survey of a representative sample of 1004 Italian citizens. Around 40% of the population perceive that strengthening the immune defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 17 publications
3
18
0
4
Order By: Relevance
“…The vast majority of the subjects had a face-to-face work modality, followed by the blended work modality. This could have a positive influence when it came to reducing the possible intake of hypercaloric foods because the prolonged stay at home could lead to anxiety and a lack of routine and, consequently, the increased consumption of this type of food as a way to relieve stress, as reflected in the studies by Savarese et al [3], Muscogiuri et al [4] and Berengui et al [18]. However, on the other hand, returning to face-to-face work prevented dedicating the recommended time to meals and their preparation processes; therefore, people consumed precooked and processed foods with scarce nutritional value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of the subjects had a face-to-face work modality, followed by the blended work modality. This could have a positive influence when it came to reducing the possible intake of hypercaloric foods because the prolonged stay at home could lead to anxiety and a lack of routine and, consequently, the increased consumption of this type of food as a way to relieve stress, as reflected in the studies by Savarese et al [3], Muscogiuri et al [4] and Berengui et al [18]. However, on the other hand, returning to face-to-face work prevented dedicating the recommended time to meals and their preparation processes; therefore, people consumed precooked and processed foods with scarce nutritional value.…”
Section: Discussionmentioning
confidence: 99%
“…This exceptional situation has been studied due to the great impact it caused at the social and health level. With regard to food consumption, a global change was observed in dietary habits due to the initial panic buying due to the lack of available food [3], as well as the consumption of processed products or foods rich in carbohydrates, because these could increase the production of serotonin and prevent depression and mood swings. Additionally, in states of low physical activity there is a tendency towards the intake of this group of foods [4], leading to a worsening in the dietary habits of the different populations studied [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The global pandemic caused by COVID‐19 has led to living conditions that promote a sedentary lifestyle, and a low quality dietary intake; increasing our vulnerability to the COVID‐19 virus 14 . The risk of cardiovascular diseases due to the SARS‐CoV‐2 pathogenic virus is believed to be aggravated by stress (affecting cortisol release rates) and sugar‐rich diets (affecting glucose release rate) 15,16 . Furthermore, patients suffering from Diabetes Mellitus are at a higher risk for complications and death from COVID‐19.…”
Section: Introductionmentioning
confidence: 99%
“… 14 The risk of cardiovascular diseases due to the SARS‐CoV‐2 pathogenic virus is believed to be aggravated by stress (affecting cortisol release rates) and sugar‐rich diets (affecting glucose release rate). 15 , 16 Furthermore, patients suffering from Diabetes Mellitus are at a higher risk for complications and death from COVID‐19. Thus, it highlights the need for self‐monitoring systems that will help with understanding the body's response to diet and keep a control on biomarker levels for this high‐risk population.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent research has shown that the buying behavior during a pandemic is, therefore, sensitive to consumer attitudes [50,51]; people's reactions to the COVID-19 pandemic vary according to personal factors, such as age [50,52], while, in the context of the COVID-19 pandemic, young people are more likely to purchase online than elderly people [53].…”
Section: Introductionmentioning
confidence: 99%